PENGARUH MEDIA PEMBELAJARAN VIDEO TERHADAP HASIL BELAJAR GULING DEPAN SMP N 03 MUKOMUKO - Zhafran Yafi Aprilianto; Gusti Handayani, Sri; Zulbahri; Novita Sari, Dessi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the issue of low learning outcomes regarding the forward roll skill among Grade VIII A students at SMPN 03 Mukomuko. Out of 32 students, only 14 (43.75%) successfully met the Minimum Mastery Criterion (KKM) of 75, while the remaining 18 students (56.25%) scored below this threshold. The study aimed to examine the impact of using video as an instructional medium on improving the students' forward roll performance. A quantitative experimental approach was employed, specifically utilizing a one-group pretest-posttest design. The study involved the entire class of 32 Grade VIII A students, selected via total sampling. Data collection relied on a performance test assessing forward roll skills, administered both before (pretest) and after (posttest) the intervention—which consisted of showing an instructional video. Data analysis utilized a paired-sample t-test to determine the difference in mean learning outcomes between the two stages. The findings indicate a significant influence of the instructional video on the students' forward roll ability; the mean score rose from 16.44 in the pretest to 22.03 in the posttest, with a significance level of p < 0.05. Thus, it can be concluded that the use of video media helped Grade VIII A students at SMPN 03 Mukomuko improve their forward roll technique. Consequently, this medium serves as a viable creative alternative for teaching physical education in schools.